Fixed-Time Synchronization for Dynamical Complex Networks with Nonidentical Discontinuous Nodes. (19th March 2021) - Qian, Xiaoliang; Liu, Qian; Li, Qingbo; Yang, Qi; Wu, Yuanyuan; Wang, Wei
Abstract : This article investigates the fixed-time synchronization issue for linearly coupled complex networks with discontinuous nonidentical nodes by employing state-feedback discontinuous controllers. Based on the fixed-time stability theorem and linear matrix inequality techniques, novel conditions are proposed for concerned complex networks, under which the fixed-time synchronization can be realized onto any target node by using a set of newly designed state-feedback discontinuous controllers. To some extent, this article extends and improves some existing results on the synchronization of complex networks. In the final numerical example section, the Chua circuit network is introduced to indicate the effectiveness of our method by showing its fixed-timely synchronization results with the proposed control scheme.